Meibography and corneal volume optical coherence tomography to quantify damage to ocular structures in children with blepharokeratoconjunctivitis. Issue 7 (25th April 2019) - Al‐Hayouti, Huda; Daniel, Moritz; Hingorani, Melanie; Calder, Virginia; Dahlmann‐Noor, Annegret
Abstract: Purpose: To evaluate non‐contact infrared meibography and anterior segment optical coherence tomography (AS‐OCT) to detect meibomian gland (MG) and corneal changes in children with blepharokeratoconjunctivitis (BKC). Methods: We acquired infrared meibography images of upper and lower lids and AS‐OCT corneal scans. One masked observer graded meiboscore, full/partial MG dropout, and measured total corneal volume and differential corneal volume per quadrant and central corneal thickness (CCT). Results: We enrolled 63 children, 31 with BKC and 32 without ocular surface inflammation; median (interquartile range) age BKC 10.6 (7.2‐13.9) years, healthy volunteers (HV) 11.4 (9.5‐13.8) years. Likert scale scores for meibography and OCT indicate no to low discomfort. Meiboscores for upper and lower lids as well as the total meiboscore were significantly higher in children with BKC than in HV. Subscores for full and partial MG dropout were also significantly higher in children with BKC than in healthy volunteers. There was no statistically significant difference between upper and lower lid for meiboscore nor full/partial MG dropout scores. The corneal volume in the superior quadrant was significantly higher in children with BKC than in HV, whereas the corneal volume in the nasal and inferior quadrants was significantly lower. Conclusions: Non‐contact imaging technologies objectively demonstrate damage to meibomian glands and changes in corneal volume secondary to BKC. The tests are well tolerated by children with mild/moderate ocular surface inflammation and can detect changes without the requirement for routine eversion of the upper lid. These parameters may be useful both for clinical follow‐up and clinical trials.